Random routing defense method based on deep deterministic policy gradient - Xiaoyu XU; Hao HU; Hongqi ZHANG; Yuling LIU (Tongxin xuebao)
To solve the problem of the existing routing shuffling defenses, such as too coarse data flow splitting granularity, poor protection effect on legitimate QoS and the security against eavesdropping attacks needed to be improved, a random routing defense method based on DDPG was proposed.INT was used to monitor and obtain the network state in real time, DDPG algorithm was used to generate random routing scheme considering both security and QoS requirements, random routing scheme was implemented with programmable switch under P4 framework to realize real-time routing shuffling with packet level granularity.Experiment results show that compared with other typical routing shuffling defense methods, the security and QoS protection effect of the proposed method are improved.